Electroacupuncture could balance the gut microbiota and improve the learning and memory abilities of Alzheimer’s disease animal model - Jing Jiang (Public Library of Science (PLoS), 2021)
Alzheimer’s disease (AD), as one of most common dementia, mainly affects older people from the worldwide. In this study, we intended to explore the possible mechanism of improving cognitive function and protecting the neuron effect by electroacupuncture. Method: We applied senescence-accelerated mouse prone 8 (SAMP8) mice as AD animal model, used Morris water maze, HE staining, 16S rDNA amplicon sequencing of gut microbiota and ELISA to demonstrate our hypothesis. Results: electroacupuncture improved the learning and memory abilities in SAMP8 mice (P<0.05) and could protect the frontal lobe cortex and hippocampus of SAMP8 mice; electroacupuncture significantly decreased the expression of IL-1β (P<0.01), IL-6 (P<0.01) and TNF-α (P<0.01 in hippocampus, P<0.05 in serum) in serum and hippocampus; electroacupuncture balanced the quantity and composition of gut microbiome, especially of the relative abundance in Delta-proteobacteria (P<0.05) and Epsilon-proteobacteria (P<0.05). Conclusion: electroacupuncture treatment could inhibit the peripheral and central nerve system inflammatory response by balancing the gut microbiota.